Pengaruh Perlakuan Pendahuluan Biji Sorgum terhadap Mutu Beras Analog - Adiba, Iffadhiya Fathin; Ridwansyah, Ridwansyah; Sinaga, Hotnida (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2026)
Rice consumption in Indonesia remains very high, highlighting the need for dietary diversification to reduce dependence on rice as the primary staple food. One potential strategy is the development of analog rice using alternative grains such as sorghum. This study aimed to evaluate the effect of different pretreatments applied during sorghum flour production on the quality characteristics of analog rice. A completely randomized design with four treatments was employed: P1 (hulled sorghum), P2 (sorghum soaked in water), P3 (sorghum soaked in 0.3% Na₂CO₃ solution), and P4 (germinated sorghum). Analog rice was produced from a composite flour consisting of sorghum flour, corn flour, and tapioca flour at a ratio of 2:1:1 (w/w/w). The resulting products were evaluated for physical properties, chemical composition, cooking characteristics, and sensory attributes. The results showed that sorghum pretreatment significantly affected (p